2001
DOI: 10.1093/gerona/56.2.b52
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation, Design, and Analysis of Gene Array Expression Experiments

Abstract: Experiments using arrays of cDNA targets to compare patterns of gene expression are beginning to play a prominent role in biogerontology, but drawing reliable conclusions from the resulting data sets requires careful application of statistical methods that discriminate chance events from those likely to reflect real differences among the samples under study. This essay discusses flaws in the logic of studies that base their conclusions on ratio calculations alone, reviews the multiple comparison traps inherent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 7 publications
2
58
0
Order By: Relevance
“…Because the number of expected false positives equals the p value percentage of the total number of comparisons tested (tests of individual genes), reducing total comparisons is useful for managing false positive error. That is, if 10,000 genes are tested at the p Ͻ 0.05 level of significance, 500 (5%) can be expected to be positive by chance alone (Miller et al, 2001). Such high false positives can rival or obscure true positives and thereby detract from statistical confidence.…”
Section: Gene Identification Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the number of expected false positives equals the p value percentage of the total number of comparisons tested (tests of individual genes), reducing total comparisons is useful for managing false positive error. That is, if 10,000 genes are tested at the p Ͻ 0.05 level of significance, 500 (5%) can be expected to be positive by chance alone (Miller et al, 2001). Such high false positives can rival or obscure true positives and thereby detract from statistical confidence.…”
Section: Gene Identification Algorithmmentioning
confidence: 99%
“…With only a few exceptions (Pletcher et al, 2002), microarray studies have not used the formal statistical analyses and sample sizes (power) necessary to estimate expected false positives or detect moderate changes in expression. Thus, given the large multiple-comparison error anticipated in microarray analyses (Miller et al, 2001), both false positive (type I) and false negative (type II) errors are often high. As corollaries, the statistical reliability of microarray results is often clouded, and many potentially important processes have likely been overlooked (Watson et al, 2000;Miller et al, 2001;Becker, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such strategies have also been proposed to deal with low power due to the Bonferroni correction. For example, for array experiments, Miller et al (2001) suggested first selecting a smaller set of microarray sample and proceeding to the second stage of tests with another data set using only genes found significant in the first stage. Later, Allison and Coffey (2002) pointed out that this two-stage method can be even more conservative if the two significance levels are not chosen carefully.…”
Section: Introductionmentioning
confidence: 99%
“…After obtaining a smaller and more promising set of markers, we conduct statistical tests with a stringently controlled overall type I error using a combination of data from the first-stage sample and the newly genotyped data. van den Oord and Sullivan (2003a) and others (Miller et al 2001;Saito and Kamatani 2002;Satagopan et al 2002) considered only new data in their secondstage test to avoid complexity in test statistics due to interdependence between the first and second samples. As argued by van den Oord and Sullivan (2003a), inclusion of first-stage data may elevate false positive discoveries, but can reduce the genotyping burden.…”
Section: Introductionmentioning
confidence: 99%